Answer:
4(3 * 39 – 12) = 5(2 * 39 + 6)
x = 39
Step-by-step explanation:
4(3x – 12) = 5(2x + 6)
(12x - 48) = (10x + 30)
12x - 10x = 30 + 48
2x = 78
2x/2 = x
78/2 = 39
x = 39
No Prob :)
It went up 24c because 25% of 96c is 24c
The answer is that (It’s 6.6)
Answer:
since the bases (X) are the same only the exponents will be subtracted and b is greater than a to get a negative exponent
Step-by-step explanation:
Shouldn't this be in the language section? But okay. I would say the simple subject would be "plane"